Cytoreductive surgery (CRS) with hyperthermic intraoperative peritoneal chemotherapy (HIPEC) versus standard of care (SoC) in people with peritoneal metastases from colorectal, ovarian or gastric origin: protocol for a systematic review and individual participant data (IPD) meta-analyses of effectiveness and cost-effectiveness. Issue 5 (12th May 2020) - Gurusamy, Kurinchi; Vale, Claire L; Pizzo, Elena; Bhanot, R; Davidson, Brian R; Mould, Tim; Mughal, Muntzer; Saunders, Mark; Aziz, Omer; O'Dwyer, Sarah
Abstract : Introduction: There is uncertainty about whether cytoreductive surgery (CRS)+hyperthermic intraoperative peritoneal chemotherapy (HIPEC) improves survival and/or quality of life compared with standard of care (SoC) in people with peritoneal metastases who can withstand major surgery. Primary objectives: To compare the relative benefits and harms of CRS+HIPEC versus SoC in people with peritoneal metastases from colorectal, ovarian or gastric cancers eligible to undergo CRS+HIPEC by a systematic review and individual participant data (IPD) meta-analysis. Secondary objectives: To compare the cost-effectiveness of CRS+HIPEC versus SoC from a National Health Service (NHS) and personal social services perspective using a model-based cost–utility analysis. Methods and analysis: We will perform a systematic review of literature by updating the searches from MEDLINE, Embase, Cochrane library, Science Citation Index as well as trial registers. Two members of our team will independently screen the search results and identify randomised controlled trials comparing CRS+HIPEC versus SoC for inclusion based on full texts for articles shortlisted during screening. We will assess the risk of bias in the trials and obtain data related to baseline prognostic characteristics, details of intervention and control, and outcome data related to overall survival, disease progression, health-related quality of life, treatment related complications and resource utilisation data. Using IPD, we will perform a two-step IPD, that is, calculate the adjusted effect estimate from each included study and then perform a random-effects model meta-analysis. We will perform various subgroup analyses, meta-regression and sensitivity analyses. We will also perform a model-based cost–utility analysis to assess whether CRS+HIPEC is cost-effective in the NHS setting. Ethics and dissemination: This project was approved by the UCL Research Ethics Committee (Ethics number: 16023/001). We aim to present the findings at appropriate international meetings and publish the review, irrespective of the findings, in a peer-reviewed journal. PROSPERO registration number: CRD42019130504.